Analysis of techniques used for teaching computer-aideddesign todesign specialists - Borysenko, D. V. (Problems of Engineer-Pedagogical Education, 2018)
Vocational training of future experts in the design sphere demands considerable methodical updates according to informational and technical development of the industry. The article considers techniques used for teaching computer-aided design to future experts in the relevant field in the process of studying specialized subjects at higher educational institutions. Techniques for teaching some disciplines using software for computer graphics and 3D development are selected and analyzed; similarities of application of methodical structures of the organization of the educational process and the author’s methods of students’ creative development through corresponding educational tasks are revealed. The optional component of the methodological content of the author's techniques and their functional practical characteristics, which are realized during computer-aided design of a design-product, are tracked. The problem field of developing students’ creativity during computer-aided design activities is defined and recommendations for further implementation of the approach to teaching computer-aided design of a design-product are suggested. The results of the suggestions for methodological optimization of teaching design specialists raise the possibility of conceptual development of innovative methodology of computer-aided design and its practical realization which has to increase the effectiveness of educational development of a design-product.